Proceedings of the 10th International Conference on Social Media and Society 2019
DOI: 10.1145/3328529.3328559
|View full text |Cite
|
Sign up to set email alerts
|

Same Same But Different

Abstract: The rise of social media platforms has changed how people interact.Mobile technologies with built-in, high-quality cameras offer new possibilities for people to document and share their everyday activities.Many consider these interaction-mediating devices to be important tools for facilitating people's social life through use of social media. The aim of this thesis is to describe what constitutes social media use in a world of smartphones with cameras, why and how social media use is meaningful as a category o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…For transparency, we clarify that the material collected for the study in 2012 has partly been reported in (Weilenmann et al, 2013). Both the 2012 and the 2017 data have been part of (Jungselius & Weilenmann, 2018; 2019) as well as the PhD thesis of the first author, presented in 2019 (Jungselius, 2019). None of these previous publications deal with nostalgia, and the examples presented in this article have not been included elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…For transparency, we clarify that the material collected for the study in 2012 has partly been reported in (Weilenmann et al, 2013). Both the 2012 and the 2017 data have been part of (Jungselius & Weilenmann, 2018; 2019) as well as the PhD thesis of the first author, presented in 2019 (Jungselius, 2019). None of these previous publications deal with nostalgia, and the examples presented in this article have not been included elsewhere.…”
Section: Discussionmentioning
confidence: 99%